La familia desde una perspectiva psicosocial en niños menores de 3 años - Cofre Casillas, Beatriz (2022)
In the present investigation, it was identified that there is psychosocial abuse in children under 3 years of age who attend the service in the Growing with Our Children modality, at the time of going to the group and individual activity, inappropriate behaviors were noted, for this reason established as an objective "to improve psychosocial relationships in families through playful activities for a good coexistence in children under 3 years of age of the care unit "CNH" Carousel de Saber" A methodology with a quantitative-qualitative approach was applied because it was used evaluation techniques and instruments such as surveys of teachers, surveys of parents and the observation sheet for children in the care unit for data collection, obtaining information in a structural way, thus giving, as a result, the lack of affectivity and co-responsibility that parents must assume with their children to receive comprehensive care that allows incorporating and Coexistence spaces guaranteeing good treatment, after these analyzes of the information it was considered pertinent to elaborate a proposal for a guide of playful activities for parents that helped to develop in the psycho-affective field through play. In this way, the application of the proposal was achieved in children, which encouraged them to improve the emotional field and therefore strengthened psychosocial relationships, improving the development of skills and abilities, as well as their motivation to carry out activities at home, strengthening a harmonious environment. and in family.